2015
DOI: 10.4028/www.scientific.net/amm.802.333
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment for Pavement Sustainable Development: Critical Review

Abstract: Certainly, one of the most cost effective and comprehensive infrastructure assets of the build environment is road infrastructure. The environmental impacts of this asset during its life-cycle drive researchers to create a foundational framework to quantify these effects. Life cycle assessment (LCA), a method for the assessment of all modules in a life cycle, has been examined to evaluate all the environmental modules and components of road projects due to constraints of environmental assessments. The enthusia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The usage and EOL stages often get less attention compared to other phases. Babashamsi et al [13] state that the use phase is often ignored due to uncertainty and insufficient information in terms of environmental impacts affecting pavement such as rolling resistance, albedo, carbonation, and leachate. Table 1 summarises the system boundaries considered by some of the highly cited pavement LCA studies.…”
Section: Goal and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…The usage and EOL stages often get less attention compared to other phases. Babashamsi et al [13] state that the use phase is often ignored due to uncertainty and insufficient information in terms of environmental impacts affecting pavement such as rolling resistance, albedo, carbonation, and leachate. Table 1 summarises the system boundaries considered by some of the highly cited pavement LCA studies.…”
Section: Goal and Scopementioning
confidence: 99%
“…The study considers a 'cradle-to-grave' scenario including a typical maintenance regime and follows the life cycle stages highlighted in Figure 1, defined as a partial LCA. The other scenarios in the use stage are omitted as there is currently incomplete supporting information to include environmental impacts of these phases [13]. The functional unit in this study, which represents the reference unit that measures the performance of the indicators, is one square-metre of pavement for the cradle-to-grave approach.…”
Section: Goal and Scope Definitionmentioning
confidence: 99%
“…Agencies are interested in reducing energy consumption, material and transportation costs, and GHG emissions seek out effective pavement recycling strategies. Babashamsi et al [7] stated that the end of life module (EOL) has been abounded by numerous of the past LCA studies (just considered 4 out of 30). The pavement can be landfilled, recycled, or covered and turned into a steady base layer for following pavement structure.…”
Section: Liturature Reviewmentioning
confidence: 99%
“…Recent review works revealed the significant increase in the research on LCA applied to road construction projects in the last twenty years [1][2][3][4]. In fact, this shows the enhancement of the sustainable strategy on the infrastructure.…”
mentioning
confidence: 99%